Smatphone user segmentation based on trust mobile payment - Vallespín-Arán, María Luisa; Molinillo-Jiménez, Sebastián; Ramos, Célia M.Q (My University, 2017)
The role of trust in mobile payment has been examined in different studies due to its importance in understanding consumer behaviour in mobile transactions,. This investigation contributes with a segmentation and a characterization of smartphone users based on their trust in mobile payment. Data was collected from 456 Spanish smartphone users and cluster analysis was employed to segment Spanish respondents. The results indicate that Spanish smartphone users can be classified into three segments depending on their trust in mobile payment. In terms of the characterization of each category, it is found that they present different demographics characteristics. While men, users aged between 25 and 34 and self-employed are overrepresented in users with high trust in mobile payment, women and users older than 45 years are overrepresented in users with low trust in mobile payment. The identified segments will allow companies to adapt their segmentation strategies.
Keywords: Informática móvil; Segmentation; Trust; Mobile payment; Smartphone